1996
DOI: 10.1107/s0108768196008294
|View full text |Cite
|
Sign up to set email alerts
|

Molecular electric moments and electric field gradients from X-ray diffraction data: model studies

Abstract: Model X-ray data sets, with and without the inclusion of experimental thermal motion parameters, have been computed via Fourier transformation of ab initio molecular electron densities for 12 different molecular crystals. These datasets were then analysed with three different multipole models of varying sophistication and, from the multipole functions, molecular dipole and second moments, as well as electric field gradients (EFG's), at each nuclear site were computed and compared with results obtained from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…An important longer-range aim of our studies is to determine experimental electrostatic parameters for biological macromolecules and to calibrate the theoretically derived electrostatic parameters used in biomolecular modeling calculations (31). Net atomic charges can, for instance, be derived experimentally from x-ray diffraction data via pseudoatom modeling (3,27,31). In analyses of small-molecule structures, spherical-atom charges refitted after multipolar refinements have been shown to yield molecular electric moments that agree well with independently measured experimental values (3,27).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…An important longer-range aim of our studies is to determine experimental electrostatic parameters for biological macromolecules and to calibrate the theoretically derived electrostatic parameters used in biomolecular modeling calculations (31). Net atomic charges can, for instance, be derived experimentally from x-ray diffraction data via pseudoatom modeling (3,27,31). In analyses of small-molecule structures, spherical-atom charges refitted after multipolar refinements have been shown to yield molecular electric moments that agree well with independently measured experimental values (3,27).…”
mentioning
confidence: 81%
“…Net atomic charges can, for instance, be derived experimentally from x-ray diffraction data via pseudoatom modeling (3,27,31). In analyses of small-molecule structures, spherical-atom charges refitted after multipolar refinements have been shown to yield molecular electric moments that agree well with independently measured experimental values (3,27). The refitted charges of the crambin peptide atoms after refinement II were: C a ϩ0.06, C ϩ0.32, O Ϫ0.18, N Ϫ0.44, H a ϩ0.08, and H N ϩ0.16 electrons.…”
mentioning
confidence: 99%
“…From the superposition Jeffrey et al (1980) 176 (50%) Savariault & Lehmann (1980) 133 (33%) Swaminathan, Craven & McMullan (1984) 490 (39%) Boese et al (1994) 89 (12%) Nijveldt & Vos (1988) 535 (26%) Destro, Marsh & Bianchi (1988) of these molecules in the unit cell, two sets of structure factors were generated; one set ('dynamic') incorporates experimental thermal motion, while the other set ('static') does not. Full details of the method have been given in a previous paper (Spackman & Byrom, 1996) and will not be repeated here. These sets of structure factors have known magnitudes and phases and, therefore, enable us to determine how well a number of structure factor models retrieve both the phases and magnitudes of Ft(H ) and, just as importantly, the errors arising from approximating ~/9 t by ~0 m in a Fourier map of Ap.…”
Section: F(h) = If(h)i Exp (I~ot(h))mentioning
confidence: 99%
“…Molecular properties derived from the multipole refined electron density are also important (Spackman & Byrom, 1996) and in Table 2 we provide estimates of the trace of the molecular second moment tensor (r 2) and the octopole moment ~ (xyz) for HMT. Clearly eigenvalue filtering applied in a routine manner as carried out here can impose a constraint which leads to a significantly worse scale factor (by as much as 7 % in this case) and hence compromise estimates of the molecular properties which are derived from the rescaled electron distribution.…”
Section: The Special Case Of Hexamethylenetetraminementioning
confidence: 99%
“…[6] It was concluded that, in general, quite reliable molecular dipole moments can be derived from multipolar modeling of diffraction data. A big advantage of estimating electrostatic moments from X-ray diffraction data is that both the size and the direction of the solid state molecular dipole moment is obtained.…”
Section: Introductionmentioning
confidence: 99%